2018
DOI: 10.1093/gbe/evy084
|View full text |Cite
|
Sign up to set email alerts
|

The Codon Usage of Lowly Expressed Genes Is Subject to Natural Selection

Abstract: Codon usage bias affects the genomes of organisms from all kingdoms of life and results from both background substitution biases and natural selection. Natural selection on codon usage to increase translation accuracy and efficiency has long been known to affect gene sequences. Such selection is stronger on highly, compared with lowly expressed genes, resulting in higher levels of codon bias within genes with higher expression levels. Additionally, selection on translation accuracy affects more strongly codons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 38 publications
(52 reference statements)
6
30
0
Order By: Relevance
“…Third, though previous studies of polymorphism data have inferred selection on synonymous sites to be weak (in keeping with Li-Bulmer), these patterns of polymorphism have also suggested a more complex selection model among 4D codons than simply preferred vs. unpreferred, contravening the model's standard formulation (Singh et al 2007;Zeng 2010;Clemente and Vogl 2012a). Fourth, there is experimental evidence that changes in one or more synonymous codons can have large phenotypic and fitness effects, suggesting that selection on CUB is not always weak (Zhou et al 1999;Carlini and Stephan 2003;Carlini 2004;Sharon et al 2018;She and Jarosz 2018;Yannai et al 2018). Indeed, experiments in yeast have found large numbers of synonymous mutations with similar fitness and phenotypic effect sizes to missense mutations, often enriched in genes with high CUB, or causing significant changes in the Codon Adaptation Index (Sharon et al 2018;She and Jarosz 2018).…”
Section: New Model Of Cubmentioning
confidence: 83%
“…Third, though previous studies of polymorphism data have inferred selection on synonymous sites to be weak (in keeping with Li-Bulmer), these patterns of polymorphism have also suggested a more complex selection model among 4D codons than simply preferred vs. unpreferred, contravening the model's standard formulation (Singh et al 2007;Zeng 2010;Clemente and Vogl 2012a). Fourth, there is experimental evidence that changes in one or more synonymous codons can have large phenotypic and fitness effects, suggesting that selection on CUB is not always weak (Zhou et al 1999;Carlini and Stephan 2003;Carlini 2004;Sharon et al 2018;She and Jarosz 2018;Yannai et al 2018). Indeed, experiments in yeast have found large numbers of synonymous mutations with similar fitness and phenotypic effect sizes to missense mutations, often enriched in genes with high CUB, or causing significant changes in the Codon Adaptation Index (Sharon et al 2018;She and Jarosz 2018).…”
Section: New Model Of Cubmentioning
confidence: 83%
“…For example, avoidance of translational errors may well shape CUB genome wide, but may be particularly important at structurally sensitive sites in proteins. The literature also continues to propose additional forces that may shape CUB [15][16][17][18][19][20], which are not well enough understood to clearly assign them as either beanbag selection or SLS. Nevertheless, the central point that different types of forces exist which have very different consequences for CUB remains valid.…”
Section: Introductionmentioning
confidence: 99%
“…The third contains genes that encode the accessory information including the singletons (unique genes) that are present in mobile genetic elements as well as in the more stable replicons (2731). The intracellular variations in codon usage can be explained on the basis of selective pressures that operate with different strengths depending on gene function and the resulting impact on cellular fitness (32). A search for the biochemical basis associated with the heterogeneity in codon usage among different gene sets has been the focus of numerous studies.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of an extensive number of genes with different functions, ubiquitousness, and degrees of phylogenetic conservation has demonstrated that codon usage is related to gene-expression level (33, 42, 43), the degree of conservation (18, 32, 44, 45), the genomic location— i. e. , chromosome, chromid, plasmidome (19, 46, 47)—and different features such as codon ramps, and mRNA secondary structure, among others (4850). Current evidence indicates that accessory genes involve atypical codon usages (21, 47, 51, 52) compared to the more conserved (ancestral) core genes in a given lineage.…”
Section: Introductionmentioning
confidence: 99%